Partnership for Schools and Building Schools for the Future: An Emerging Strategy? - Soulsby, Christopher David (2009)
This dissertation investigates the strategy adopted by Partnership for Schools (PfS) to meet the Government‟s commitment to build schools fit for the 21st century. The Government‟s intention was that the programme: Building Schools for the Future (BSF) would be not just be about good buildings but also lead to improvements in educational performance. The rationale lying behind this „twin track‟ approach is examined. The state of the school estate at the end of the twentieth century, and the chronic lack of investment, is exposed. The commonly held belief that improving school buildings would lead to improvements in educational standards is also discussed. Existing literature is examined to see if there is any basis for this belief, and it is established that, certainly from the qualitative research carried out, that a link can be made. Quantitative research into the link is found to be much more inconclusive in its findings, and the best that can be said is that this does not find any evidence to the contrary. The findings are that the strategy adopted by PfS, although failing to meet initial targets regarding the number of completed schools, has now started to show success. The dissertation examines how this strategy has led to the centralisation of power around PfS over the building procedures, but also discusses how the erosion of power away from local authorities has been reversed in part. By interviewing a number of key stakeholders, the picture of an emerging strategy within the BSF programme is constructed. The study also finds that there is a distinct lack of detailed guidance as to what schools must do in order to improve standards, and that, with the exception of headteachers, teachers have been the least involved of all the stakeholders in the BSF process. The final conclusion is that new buildings provide the opportunity for improving pupil performance, but it is good school leadership that drives change, and teachers that effect it.